2007
DOI: 10.1021/pr070153m
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Proteins Secreted by Trichophyton rubrum and Trichophyton violaceum under in Vitro Conditions

Abstract: Dermatophytes cause most superficial mycoses in humans and animals. Their pathogenicity is probably linked with the secretion of proteins degrading keratinised structures. Using 2D-PAGE and a shotgun mass spectrometry approach, we identified 80 proteins from Trichophyton rubrum and Trichophyton violaceum secretomes, under conditions mimicking those in the host. Identified proteins included endo- and exoproteases, other hydrolases, and oxidoreductases. Our findings can contribute to a better understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 43 publications
4
36
0
Order By: Relevance
“…For instance, in other fungi, such as Aspergillus spp. and dermatophytes, multiple proteases are concomitantly secreted in culture supernatant and are not degraded (13,33). In addition, the acquisition of the correct three-dimensional structure may protect secreted proteins from proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in other fungi, such as Aspergillus spp. and dermatophytes, multiple proteases are concomitantly secreted in culture supernatant and are not degraded (13,33). In addition, the acquisition of the correct three-dimensional structure may protect secreted proteins from proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…By two-dimensional polyacrylamide gel electrophoresis and a shotgun mass spectrometry approach, secreted proteins from T. rubrum and T. violaceum were identified in soy culture supernatants, including endo-and exoproteases and other hydrolases (8). Such analyses of proteolytic dermatophyte supernatants, however, are limited to the identification of secreted proteins.…”
mentioning
confidence: 99%
“…Although we cannot overlook the facts that alkaline proteins are more difficult to process than acidic ones and that small proteins are easily lost, we can still hypothesize that secreted proteins are preferentially acidic and of high MW. Indeed, published secretomic results on various fungal species have confirmed that most protein spots resolve within these acidic ranges [15-19, 21, 22], with few exceptions reporting secreted proteins that were well resolved across the entire 3-10 pH range [14,23]. Instead of reducing the volume of biological material as previously achieved though UF, we increased the volume capacity of the centrifuge tubes.…”
Section: Optimizing the Extraction Of Highly Diluted Secreted Proteinmentioning
confidence: 85%
“…Yet, several studies on fungal secretomics used TCA/acetone method to precipitate proteins from liquid media [14,18,19,23], with one study reporting the use of TCA in water followed by multiple ethanol washes [15]. Here, protein content could not be assayed; however, 1-and 2-D profiles were improved and showed intense bands corresponding to 266 spots (Fig.…”
Section: Optimizing the Extraction Of Highly Diluted Secreted Proteinmentioning
confidence: 99%